Driving Sustainable Popcorn Breeding for Drought Tolerance in Brazil - Kamphorst, Samuel Henrique; do Amaral Junior, Antônio Teixeira; de Lima, Valter Jário; Carena, Marcelo Javier; Azeredo, Valdinei Cruz; Mafra, Gabrielle Sousa; Santos, Pedro Henrique Araújo Diniz; Leite, Jhean Torres; Schmitt, Kátia Fabiane Medeiros; dos Santos Junior, Divino Rosa; Bispo, Rosimeire Barboza; Santos, Talles de Oliveira; et al. (Frontiers in Plant Science, 2021)
Drought has currently hit several regions worldwide and tends to be more frequent due to climate change. It might compromise food security and the economic structure related to agribusiness. Popcorn has a crucial role in the Brazilian economy, but cultivars adapted to water stress, the most prejudicial abiotic stress for crop productivity, are unknown to date. Given this scenario, knowing the genetic basis of agronomic traits under stress conditions is essential in promoting crop productivity and plant adaptation. Under two contrasting water conditions (WC) and different crop seasons (CS), we aimed to generate information about combining ability of 10 popcorn progenitors and 15 hybrids which were obtained by circulating diallel. The water stress started at male pre-anthesis stage. Owing to significant interactive effects genotype (G)*CS, G*WC, and G*CS*WC, we expect a differential response of popcorn inbred lines and hybrids to CS and WC. Moreover, we highlight the influence of WC on progenitors’ average performance across crosses and dominance deviations. Regardless of CS and WC, non-additive effects controlled grain yield (GY), grain number per row (GN), ear length and diameter (ED), and 100-grain weight. On the other hand, additive effects had supremacy on popping expansion (PE). For each CS, regardless of WC, the cause-effect of GN (2018) and ED (2020) on GY seem to be a great opportunity for indirect selection. Using hybrids is a good opportunity for obtaining superior genotypes for GY and its components. However, the selected progenitors must be above-average for PE. We recommend the L76 x L61 hybrid for the Brazilian agribusiness due to greater productivity and dominance deviations.